Pengaruh Religiusitas, Label Halal, dan Harga terhadap Keputusan Pembelian Konsum Muslim di Kabupaten Jember - Amaliyan Najah; Lilis Yuliati; N. Ari Subagio; Ati Musaiyaroh (Muttaqien, 2025)
Everyone has preferences in choosing food, one of the favorite foods of Indonesian people is noodles. As a society with a Muslim majority, it is certainly important to know and practice Islamic teachings, including in choosing food, of course, halal is the right choice. This study analyzes the influence of religiosity variables, halal labels, and prices on purchasing decisions for spicy noodles. The method used is quantitative, analyzing data through numbers through questionnaires. The analysis used is multiple linear regression with partial t and simultaneous f hypothesis tests. The results of the study indicate that the variables of religiosity, halal labels, and prices have a significant effect both partially and simultaneously. The results of this study are expected to contribute to academics purchasing decisions and can also be used as a guideline for further research. This study is also likely to be used as a reference for companies or producers of spicy noodles for strategies in attracting consumers.